Research Trend on Crop Diversification in Enhancing Food Security - Hertini, Etty Sri; Haras, Abdul Fajar; Lubis, Mitra Musika; Haryono, Haryono (West Science Agro, 2024)
This study employs bibliometric analysis to explore the global research landscape of crop diversification, highlighting the significant contributions and collaborations among countries in addressing the challenges of agricultural sustainability and food security. Through the utilization of VOSviewer, the research maps out intricate networks of international collaborations and identifies key regional and global players in the field. The findings illustrate a robust pattern of interconnected research efforts, with the United States, India, and the United Kingdom acting as central hubs. The study reveals the interdisciplinary nature of crop diversification research, incorporating aspects of genetics, soil science, and climate change adaptation. Despite robust collaborations, the study also addresses challenges such as resource disparities between developed and developing nations and cultural and regulatory barriers that could hinder effective knowledge exchange. The conclusion emphasizes the need for equitable research partnerships and the integration of advanced agricultural technologies with traditional practices to enhance food security in a changing climate.